MANAJEMEN PEMBELAJARAN IPA SISWA SD DENGAN MENERAPKAN MODEL INKUIRI - Siti Mihayati (Manajer Pendididikan, 2016)
The purpose of this research was to describe learning management by applying inquiry model. The subjec of this research was student fifth class at SD Negeri 04 Kepahiang. Theinstrument of this reseach used student sheet, individual test, student respon of test, and the student observation of sheet. Base on this reseach in cycle I, II, and III has been improve in the student result of learning, by the average value was 5,5 but clasicaly presentage was quite with 20% the student get score 60. The student activity in learning process improved for each cycle were 20%, 85%, and 90%. So that learning management with inqury model could be the alternatife to improve the student resut of science learning.Keywords: learning, management, inquiry, science.